(untitled) (MAUSAM, 1957)
The present state of our knowledge of microseisms is summarised. A study of the microseisms recorded by the Seismological Observatories at Calcutta, Hyderabad, Kodaikanal, New Delhi and Poona, during the passage of the Bombay cyclone of November 1948;Andhracyclone of October 1949 and the Bay cyclone of December 1951, is presented. The results show that microseisms of significant amplitudes are recorded at all the stations only when the region of low pressure at sea reaches the stage of a cyclonic storm. The amplitudes then rise and fall simultaneously at all the Indian stations, reaching the maximum value at the same time. Microseisms are not recorded for all positions of the storms. The periods of microseisms generally show arise with increasing amplitudes and seem to have no dependence on the distance.